In the eye of the beholder? The returns to beauty and IQ for the self‐employed. (24th June 2019) - Patel, Pankaj C.; Wolfe, Marcus T.
Abstract: Research Summary : Using a two study approach, we examine the relationship between attractiveness and key aspects of self‐employment. In Study 1, in which individuals rated the attractiveness of participants at the beginning of the interview, our results indicate that self‐employed males are more likely to be attractive and that more attractive self‐employed males have higher incomes. In Study 2, our findings indicate that at low levels of attractiveness, higher IQ self‐employed males have higher incomes in 1974; however, differences in income from IQ declined as attractiveness increases. We do not find differences for either outcome for females in either study. Managerial Summary : This research investigates the relationship between attractiveness and self‐employment. The results indicate that self‐employed males are more likely to be considered attractive than their female counterparts, and that attractive self‐employed males have higher incomes than self‐employed males who were not considered attractive. Additionally, our results reveal that IQ is positively associated with income for less attractive self‐employed males, however this relationship decreases in strength as attractiveness increases. Interestingly, our results do not indicate that attractiveness influences either the likelihood of self‐employment, or performance within self‐employment, for females. Our findings highlight the importance that attractiveness can play within the self‐employment process, as well as the relevance of considering the role that social norms regarding gender might have in determining who pursues, and is successful in, self‐employment.